The effect of picloram concentrations and explants types on the induction of somatic embryo on North Aceh Cocoa genotype - . Zuyasna; Siti Hafsah; Rahmi Fajri; M. Ovan Syahputra; Gilang Ramadhan (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
.  The effect of picloram concentrations and three explants types on cacao somatic embryogenesis was studied. The objective of this work was to evaluate a procedure for somatic embryogenesis of cacao (Theobroma cacao L.) Aceh clones. Somatic embryogenesis was induced using floral tissue explants (petal, staminode, and anther) on North Aceh cacao genotype. No growth was observed on petal types of explants on low concentrations of picloram. Depending on the explants, the percentage of explants producing one or more embryos ranged from 3% to 75%, 5% to 80%, and 10% to 90% on media containing 3 mg/l, 4 mg/l, and 5 mg/l picloram respectively. Staminode explants produced 3 to 10 times more somatic embryos than petals, while anthers produced 2 to 5 times.  Secondary embryos were induced from the floral explants of the North Aceh cacao genotype that exhibited efficient primary embryogenesis. Percentage embryogenesis generally increased with culture time